Dilated Cardiomyopathy Mutation (R134W) in Mouse Cardiac Troponin T Induces Greater Contractile Deficits against α-Myosin Heavy Chain than against β-Myosin Heavy Chain - Gollapudi, Sampath K.; Chandra, Murali (Frontiers in Physiology, 2016)
Many studies have demonstrated that depressed myofilament Ca2+ sensitivity is common to dilated cardiomyopathy (DCM) in humans. However, it remains unclear whether a single determinant — such as myofilament Ca2+ sensitivity — is sufficient to characterize all cases of DCM because the severity of disease varies widely with a given mutation. Because dynamic features dominate in the heart muscle, alterations in dynamic contractile parameters may offer better insight on the molecular mechanisms that underlie disparate effects of DCM mutations on cardiac phenotypes. Dynamic features are dominated by myofilament cooperativity that stem from different sources. One such source is the strong tropomyosin binding region in troponin T (TnT), which is known to modulate crossbridge (XB) recruitment dynamics in a myosin heavy chain (MHC)-dependent manner. Therefore, we hypothesized that the effects of DCM-linked mutations in TnT on contractile dynamics would be differently modulated by α- and β-MHC. After reconstitution with the mouse TnT equivalent (TnTR134W) of the human DCM mutation (R131W), we measured dynamic contractile parameters in detergent-skinned cardiac muscle fiber bundles from normal (α-MHC) and transgenic mice (β-MHC). TnTR134W significantly attenuated the rate constants of tension redevelopment, XB recruitment dynamics, XB distortion dynamics, and the magnitude of length-mediated XB recruitment only in α-MHC fiber bundles. TnTR134W decreased myofilament Ca2+ sensitivity to a greater extent in α-MHC (0.14 pCa units) than in β-MHC fiber bundles (0.08 pCa units). Thus, our data demonstrate that TnTR134W induces a more severe DCM-like contractile phenotype against α-MHC than against β-MHC background.